Dynamic Income, Progressive Taxes, and the Timing of Charitable Contributions - Randolph, William C. (Journal of Political Economy, 1995)
Using an econometric model of charitable giving and a 10-year panel of tax return data, I find that previous studies have underestimated the effects of permanent income and overestimated the effects of permanent changes in tax prices. The significant statutory tax changes that occurred during the 1980s, especially in 1986, serve to identify the key model parameters. My results imply that people smooth their giving when transitory income changes but also time their giving to exploit transitory changes in tax prices. The results also raise questions about how effectively the tax incentives permanently influence the level, rather than just the timing, of charitable giving by individuals.